NONINVASIVE MEASUREMENT OF EARLY ATHEROSCLEROSIS BY HIGH-RESOLUTION B-MODE ULTRASONOGRAPHY - Halenka, Milan (Biomedical papers, 1999)
Development of sophisticated noninvasive methods permits the identification of asymptomatic subjets withearly atherosclerosis. High-resolution B-mode ultrasound measurement of the intima-media thickness (IMT) is asafe and reproducible way of quntifying early changes in the arterial wall, mainly in the carotid arteries. Increasedcarotid IMT is associated with major cardiovascular risk factors and seems to be a powerful predictor of cardiovascularevents, especially coronary artery disease.
Keywords: Early atherosclerosis / Intima-media thickness / B-mode ultrasound imaging / Cardiovascular risk factors